Relation between release parameters and throwing distance of the javelin throw - Murakami, M.; Ishikawa, M.; Tanabe, S.; Ito, A. (ISBS Proceedings Archive (Michigan), 2018)
The present study undertook three-dimensional examination of release parameters and throwing distances, in order to understand the initial flight characteristics of the javelin throw. 57 right-handed javelin throwers were investigated. The measured throwing distances ranged from 45.25 m to 87.17 m. The elite throwers had a tendency to significant positive correlation between theoretical distance and initial velocity of javelin release. Throwers who achieved throwing distances of over 70m were observed to have throwing distances that were shorter than their theoretical distances, while those whose throwing distances were under 70 m group displayed throwing distances that were longer than their theoretical distances. When the data were applied to initial velocity of javelin release, it was equivalent to 26 m/s.